Building Law Enforcement with Character Ulil Albab: Reflection of Godly Values in The National Legal System - Fathurrahim; Syafari, Tri (Journal of Legal Contemplation, 2025)
In law enforcement, moral aspects are very important in the court process. regarding law enforcers with the character of ulil albab which will be used as the basis for study to reflect divine values in the national legal system. the purpose of this study is: how to build law enforcers with the character of ulil albab: reflection of divine values in the national legal system. this type of research is qualitative research that is descriptive analytical, namely legal research where knowledge or theory about the object already exists and wants to provide a picture of the object of research. The results of this study can be seen from the ten main characteristics of ulil albab humans who can make a significant contribution to fair and civilized law enforcement, as Allah SWT has conveyed in the Qur'an. The concept of ulil albab is very relevant to be applied in the world of education. These characteristics can build a generation that is intellectually intelligent, but also has high moral and spiritual integrity. Thus, education that prioritizes the values of ulil albab will produce individuals who are able to collaborate positively for society and the nation.